Successful long-term use of Gellhorn pessary and the effect on symptoms and quality of life in women with symptomatic pelvic organ prolapse. Issue 2 (February 2019) - Mao, Meng; Ai, Fangfang; Kang, Jia; Zhang, Ye; Liang, Shuo; Zhou, Ying; Zhu, Lan
Abstract: Objective: To evaluate the long-term continuation rate of the Gellhorn pessary and its effect on bothersome symptoms and quality of life (QOL) in women with symptomatic pelvic organ prolapse (POP). Methods: This was a prospective observational study. Ninety-one women with symptomatic POP were successfully fitted with Gellhorn pessaries (short stem) between June, 2015 and January, 2017. The participants were monitored at 3 and 6 months, and also every 6 months afterwards until February, 2018. Prolapse and urinary symptoms were assessed, and the Pelvic Floor Distress Inventory-20 (PFDI-20) and Pelvic Floor Impact Questionnaire-7 (PFIQ-7) were administered at baseline and at each follow-up visit. Logistic regression was performed to identify independent predictors of discontinued pessary use. McNemar's test and paired t tests were used to evaluate the changes in symptoms and QOL in the continuation group. Results: In this study, 58.3% of participants continued to use the pessaries after a median follow-up time of 23.5 months. A total vaginal length <7.5 cm (odds ratio 0.03, 95% confidence interval 0.00-0.35, P = 0.01) was an independent predictor of pessary discontinuation. In the continuation group, almost all prolapse and voiding difficulty symptoms were resolved at the study endpoint. The changes in the urinary and prolapse scales of both the PFIQ-7 (mean [SD] changes were −21.2 [26.6] in the urinary scale and −32.5 [29.5] in the prolapse scale) and PFDI-20 (mean [SD] changes were −15.3 [21.3] in the urinary scale and −29.8 [22.8] in the prolapse scale) achieved clinical significance (effect size >0.5). Conclusions: More than half of the patients continued long-term use of the pessary. The Gellhorn pessary can resolve prolapse and voiding difficulty symptoms effectively. In addition, the Gellhorn pessary can significantly improve the QOL of women via long-term use. However, the Gellhorn pessary has a limited effect on defecatory symptoms.